A report of two cases of splenectomy in children younger than two years old with hereditary spherocytosis - Sheng Jin; Yeming Wu (Elsevier, 2015)
Hereditary spherocytosis (HS) is a common pediatric hemolytic anemia and one of the most common types of familial hemolytic anemia caused by congenital red blood cell defects. HS often presents clinically as childhood anemia, jaundice, and progressive splenomegaly. It is generally accepted that splenectomy is the most effective treatment for HS, but development of overwhelming infections with symptoms such as chills, high fever, and septicemia may occur because of immune dysfunction after splenectomy. As a result, the generally proposed age for children to undergo splenectomy is after 5 years of age. Splenectomy in younger HS patients is rarely reported. Here, however, we report 2 cases of HS in children younger than 2 years of age (15 months and 18 months) who underwent splenectomy; we also report on their follow-up.